PEMANFAATAN DAN PENATAAN RUANG TEPI SUNGAI KRUENG ACEH KOTA BANDA ACEH - Rahmat Rahmat; Izziah Izziah; Sofyan M. Saleh (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Krueng Aceh River which is flow passes the center of Banda Aceh city. Krueng Aceh River become an integral part for the growth and development of Banda Aceh City, which has a strategic role in support urban activity and has enormous beauty potential in shaping image of the city and improving the quality of open space in Banda Aceh City. Krueng Aceh river is an element of public spaces that can be a basis for development of waterfront city. In arrangement and development of riverside as waterfront city area is not running maximally and worried not accordance with the direction from Spatial Plan. The utilization of the space on the Krueng Aceh River is not well organized and maximal. This research purpose is to identify how to utilize the space of waterfront area of Krueng Aceh river on the Spatial plan of Banda Aceh City in 2009-2029, formulate a structuring optimization strategy and development of waterfront area of Krueng Aceh river as the waterfront city area of Banda Aceh. Method used is descriptive method with combination research approach (mixed method) where the qualitative data supported by quantitative data processing. Method used to measurement is Likert Scale also data analysis by SWOT analysis on the primary and secondary data. Results of SWOT analysis obtained three alternative strategies which are: 1) Issuing regulation in form of local regulation as derivative from the Spatial Plan of Banda Aceh City in 2009-2029 which reinforces riverside function of Krueng Aceh River to become waterfront area and implement it as guidelines and consequent, 2) Optimize the utilization of space on waterfront area of Krueng Aceh area by arranging and developing the area, 3) Improve management and control in arrangement and developing waterfront area of Krueng Aceh river.